Effectiveness of Local Tax Collection in Manado City - Lamia, Ketty; Tumbel, Goinpeace H; Tarore, Steven V (JUPE : Jurnal Pendidikan Mandala, 2023)
This research discusses the effectiveness of local tax collection in Manado City.  This research aims to provide a more comprehensive insight into how hotel and restaurant taxes are managed, collected, and used by local governments to obtain optimal revenue. In this study, the authors used a qualitative approach as the main method of collecting data. This method allows the author to gain first-hand understanding and experience from various stakeholders, such as taxpayers, tax officers, and local governments. Through in-depth interviews, observations, and document analysis, the author explores the factors that affect the effectiveness of hotel and restaurant tax collection comprehensively. This research is expected to make an important contribution to the understanding of the effectiveness of hotel and restaurant tax collection, as well as provide useful recommendations for local governments in increasing local revenue through more effective tax collection